Region-specific expression of circular RNAs in the mouse brain. (14th February 2018) - Chen, Bei Jun; Yang, Belinda; Janitz, Michael
Highlights: Circular RNAs show distinct expression pattern in hippocampus and prefrontal cortex. CircRNAs are expressed independently from their linear RNA counterparts. CircRNAs are expressed more abundantly in the hippocampus. Specific hotspot genes express numerous circRNA isoforms in different brain regions. Abstract: Circular RNAs (circRNAs) are abundant in mammalian brain and their expression is regulated in a tissue- and developmental stage-specific manner. Mammalian brain is the most transcriptionally complex organ. While many studies have extensively studied linear transcriptome and its biological functions in the brain, the circular transcriptome remains largely unexplored. This study focused on investigation of circRNA expression patterns in the mammalian brain regions critical for cognitive and memory functions and performed comparative analysis with the linear transcriptome. Altogether our study showed that circular and linear RNAs have independent expression patterns despite being derived from the same genomic locus, and that circular transcriptomes from different brain region have distinct characteristics in terms of transcript abundance and composition.